KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA DIRINJAU DARI TIPE KEPRIBADIAN FLORENCE LITTAUER - kodai, Muhaimin; Badu, Syamsu Qamar; Yahya , Lailany (LPPM Universitas Bina Bangsa, 2024)
The role of mathematics is not only to involve students in understanding the material thoroughly, but also to train them to think creatively and logically and to be able to carry out mathematical skills with daily activities, which is known as Concept Understanding Ability. This research aims to describe students' conceptual understanding abilities in solving mathematics problems on fractional numbers based on Florence Littauer's personality type. The research method used is descriptive with a qualitative approach. Data was collected through tests of students' mathematical literacy skills and interviews. The research subjects were two class VII students at MTs Nurul Bahri for the 2023/2024 academic year who were selected based on personality type. The data obtained was then analyzed qualitatively by paying attention to indicators of the ability to understand mathematical concepts